Cellular Metabolites Enhance the Light Sensitivity of Arabidopsis Cryptochrome through Alternate Electron Transfer Pathways . Issue 11 (26th November 2014) - Engelhard, Christopher; Wang, Xuecong; Robles, David; Moldt, Julia; Essen, Lars-Oliver; Batschauer, Alfred; Bittl, Robert; Ahmad, Margaret
Abstract : In vivo analysis of cryptochromes revealed that these blue light receptor flavoproteins undergo significant changes in light sensitivity resulting from interactions with cellular metabolites. The results support a mechanism of flavin reduction in cryptochrome signaling and provide a paradigm for studying flavoprotein photochemistry in an intracellular environment. Abstract: Cryptochromes are blue light receptors with multiple signaling roles in plants and animals. Plant cryptochrome (cry1 and cry2) biological activity has been linked to flavin photoreduction via an electron transport chain comprising three evolutionarily conserved tryptophan residues known as the Trp triad. Recently, it has been reported that cry2 Trp triad mutants, which fail to undergo photoreduction in vitro, nonetheless show biological activity in vivo, raising the possibility of alternate signaling pathways. Here, we show that Arabidopsis thaliana cry2 proteins containing Trp triad mutations indeed undergo robust photoreduction in living cultured insect cells. UV/Vis and electron paramagnetic resonance spectroscopy resolves the discrepancy between in vivo and in vitro photochemical activity, as small metabolites, including NADPH, NADH, and ATP, were found to promote cry photoreduction even in mutants lacking the classic Trp triad electron transfer chain. These metabolites facilitate alternate electron transfer pathways and increase light-induced radical pair formation. We conclude that cryptochrome activation is consistent with a mechanism of light-induced electron transfer followed by flavin photoreduction in vivo. We further conclude that in vivo modulation by cellular compounds represents a feature of the cryptochrome signaling mechanism that has important consequences for light responsivity and activation.